Analysis of AI integration in English language learning in an International elementary school in Indonesia: A case study - Elsa Ro'is Hamzani; Ella Wulandari (Universitas Tidar, 2026)
The use of artificial intelligence (AI) in various sectors, including education, has been widespread. An international school that prioritizes bilingualism, an integrated curriculum, and learning facilities has actively adopted technology in its learning process. This study focuses on (1) understanding how AI is used to support the learning process, (2) the impact of the use of AI on student motivation, and (3) understanding the advantages and disadvantages of AI in English learning. This study uses a qualitative approach with a case study design. Data collection techniques used semi-structured interviews and mini-observation. A participant of this study is a teacher at an international elementary school who used an AI learning process. Data were analyzed using thematic analysis to obtain themes that emerged from the data findings. This study found that the use of AI in international elementary schools is high, with several AI-based applications such as Grammarly, MagicSchool AI, Canva AI, Word Wall, Twinkl, and YouTube. The use of AI in learning can also increase student motivation and enthusiasm. Easy access and abundant references are benefits offered by AI. Although accompanied by the disadvantage that this causes dependence. It is hoped that this research can be a reference source for other schools wishing to implement AI in learning.